Polymorphisms in Dopamine Transporter (SLC6A3) are Associated with Stimulant Effects of d-Amphetamine: An Exploratory Pharmacogenetic Study Using Healthy Volunteers - Hamidovic, Ajna (Behav Genet, 2010)
Individuals vary in their subjective responses to stimulant drugs, and these differences are believed to be partially genetic in origin. We evaluated associations between mood, cognitive and cardiovascular responses to d-amphetamine and four polymorphisms in the dopamine transporter (SLC6A3): rs460000, rs3756450, rs37022 and rs6869645. Healthy Caucasian male and female volunteers (N = 152) participated in a double-blind, crossover design study in which they received placebo, 10 and 20 mg of d-amphetamine. We measured self-reported rating of mood, performance on the Digit Symbol Substitution Task, blood pressure and heart rate. Individuals with the C/C genotype at rs460000 (N = 83) reported approximately twofold higher ratings of stimulation and euphoria relative to the A/A+A/C (N = 69) genotype group, at both the 10 and 20 mg doses. No other responses or SNPs showed significant effects. rs460000 is in perfect LD with rs463379 (CEU: D′ = 1; r(2) = 1), which was not studied here, but has been associated with etiology of Attention Deficit Hyperactivity Disorder (ADHD). These findings suggest a pleiotropic effect of this polymorphic locus on both ADHD and sensitivity to the subjective effects of amphetamine.